Intensive Management of Teak (Tectona grandis) Plantations under Irrigation on Farm Land - some Observations - Haque, M. S. (Indian Forester, 1996)
The paper deals with the technical feasibility and financial viability of intensive, irrigated Teak plantations. The author has based his observations after visiting such plantations in Periyar District of Tamil Nadu. He suggests that intensive, irrigated Teak plantations may not have the qualities for which teak is famous, but definitely such wood has a ready use in an otherwise wood starved market. He further recommends that such schemes are not only technically feasible but also financially viable and are eligible for availing of institutional finance, if raised for development of wastelands. IRR of such schemes exceed 30%.